Зүүн-Хойд Азийн бүс нутгийн аюулгүй байдлын асуудал - Д. Бумдарь (Politology, 2024)
In the 21 century safety and security is becoming increasingly difficult for states to determine a way to prevent potential problems and crisis. Globalization is one of the main causes. According to international relations theory, realists believe that globalization is the fundamental source of conflict, but liberals believe that it will create political convergence with the states government in the future. Furthermore, the impact of globalization on international communication system and a regional security has a positive and negative effects. This causes security increase and re-design preventive way for states government to be improved. It can be said that international relations and the regional balance of power problems can face danger and lose stability due to globalization. Crisis management and its strategy must be able to anticipate and predict crisis. Хураангуй: Зүүн-Хойд Азийн бүс нутагт Япон, Хойд Солонгос, Өмнөд Солонгос, Монгол, БНХАУ, ОХУ зэрэг улсууд багтдаг дэд бүс нутаг. Гэхдээ БНХАУ, Япон, Хоёр Солонгос бол газарзүйн хувьд ч, түүхэн болон соёлын хувьд ч энэ бүс нутгийн цөм гэж үздэг. ОХУ нь Алс Дорнод, Дорнод Сибирийн нутаг дэвсгэрээрээ энэ бүс нутагт багтдаг. Энэ бүс нутгийн улс орнуудын эрх ашгийг тэгш хангаж чадахуйц бүс нутгийн аюулгүй байдлын тогтолцоо хараахан бүрэлдэж тогтоогүй байна. Энд Америк болон түүний холбоотнуудын ашиг сонирхолд үйлчилсэн өмнөх үеийн хатуу тогтолцоо оршиж байгаа хэмээн судлаачид үздэг. Энэхүү судалгааны өгүүлэлдээ бүс нутгийн тухай ойлголт, Зүүн-Хойд Азийн бүс нутгийн улс орнуудын байр суурь, аюулгүй байдлын асуудлыг харьцуулан шинжлэхийг зорьсон болно.